Dare to Dream: Promoting Indigenous Children's Interest in Health Professions through Book Collections. - Clar, Monique; Drouin, Éric; Iverson, Sandy (Journal of the Canadian Health Libraries Association (JCHLA), 2018)
Introduction: Indigenous peoples in Canada experience significant health challenges, but few pursue careers in the health sciences. Two programs by medical librarians designed to encourage children in First Nations communities to develop an interest in science and health and to dream of careers in the health professions will be presented. Description: An academic library in the province of Quebec developed children's health and science book collections with Indigenous school libraries. Library and information science students, as well as a librarian, participated in health education activities in the recipient schools. This project inspired the community service project of the joint MLA/CHLA-ABSC/ICLC Mosaic|Mosaïque 2016 conference, which focused on placing similar collections in Ontario Indigenous communities. The mechanics, benefits, and challenges of the programs will be discussed including book selection and delivery. Outcomes: Hundreds of books have been delivered and informal qualitative evaluative data from the recipient communities indicates that the programs have been very well received. Some difficulties in providing optimal access to the books were identified due to communication problems or the relative lack of library infrastructure in these communities. Discussion: Reading for pleasure is linked to student's academic success. Access to varied and quality literature is important for school achievement, therefore these collections may potentially impact student's future life chances. While a direct correlation between these collections and student's future career choices cannot be easily measured, it is known that Indigenous high school graduates frequently choose to pursue professions linked to the needs of the community. Therefore any materials drawing attention to potential community health needs or encouraging interest for health sciences may well influence students' choices.